Peran Guru dalam Pembelajaran Daring Untuk Meningkatkan Hasil Belajar PAI pada Masa Pandemi Covid 19 di Sekolah Dasar No. 1 Seminyak - Mahmudah, Mahmudah; Rusmayani, Rusmayani; Arifin, Haris Nursyah (Faidatuna, 2020)
The world of education in indonesia is currently experiencing a change in services due to the covid 19 pandemic and is required to make changes to the way of teaching, and other administrative services in the context of the indonesia education world, the massive changes in services resulting from the impact of the covid 19 pandemic have greatly disturbed students, teachers and parents. They are required to make changes to the way of teaching and learning and guide quickly and accurately.The role of the teacher is now very important because the learning prosess cannot be faceto-face anymore. The teacher must really do everything possible so that students can understand the material presented online.This study aims to determine:( 1) the role of teachers in improving PAI learning outcomes during the covid 19 pandemi at SD No. 1 Seminyak for the 2019/2020 school year, (2) learning outcomes during the covid 19 pandemi at SD No. 1 Seminyak 2019/2020 academic year, (3) inhibiting and supporting factors in the implementation of online learning in Islamic education subjects during the covid 19 pandemic at SD No. 1 Seminyak in the school year 2019/2020.This type of research is descriptive kwalitatif, the informan is determined by purposive method, while the key informants are the principel, religion teacher, home room teacher, students, student guardians and the data committee is analyzed by data reconstruction stages, data presentation, and verification conclusion.The results showed; (1) teachers are require to play a deeper role in online learning during the covid 19 pandemi, the online learning process delivered material through learning videos in the whatsap grop, make google absences from monitoring students to memorize short surahs via whatsapp or video calls to provide motivation and encouragement to students. (2) Pai's study results during the covid-19 pandemic are less than maximal because teachers cannot monitor students directly and many obstacles in online learning. (3) supporting factors in the implementation of online learning, namely, the availability of mobile quota and internet networks. While the inhibiting factor in online learning, namely, aconomi limitations, internet network is sometimes not as stable.